THE PREVALENCE OF STRESS AMONG INTERIOR DESIGN AND FURNITURE STUDENTS - Alawad, Abeer A; Slamah, Aml A (European Scientific Journal, ESJ, 2014)
This study investigated the stressors experienced by students and aimed to determine the most prevalent cause of stress amongst university students studying Interior Design and Furniture. In addition, consideration was given to whether sources of stress differ depending on the students’ year of study. The sample consisted of 59 female students from the second, third and fourth years of the Interior Design and Furniture course in the Housing Department, Faculty of Home Economics, at King Abdulaziz University, Jeddah. The method of investigation was a questionnaire which classified stress into three main themes: academic factors, environmental factors and personal factors. The results indicate that the largest source of stress for students was academic factors, while the most prevalent stressor was academic overload. Other stressful academic factors included unclear evaluation criteria, assessment deadlines, faculty absence during office hours and shortage of course references. A major environmental factor causing stress was linked to finding a studio environment and also a place to store work and equipment. The principal stressors regarding personal factors were fear of failure and concern about their future career. Most notably, there is no significant differences between different year levels in respect to the stress level p>0.05.